2021
DOI: 10.1007/s00431-021-04155-3
|View full text |Cite|
|
Sign up to set email alerts
|

Autopsy and pre-mortem diagnostic discrepancy review in an Irish tertiary PICU

Abstract: Review ante- and post-mortem diagnoses and assign a Goldman error classification and establish autopsy rates. A retrospective analysis of autopsies performed on patients who died in paediatric intensive care unit (PICU) between November 13, 2012, and October 31, 2018. We reviewed medical and autopsy data of all patients, and Goldman classification of discrepancy between ante- and post-mortem diagnoses was assigned. Tertiary PICU. All patients that died in PICU within the designated timeframe. Goldman error cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…In their study M. O'Rahelly et al observed a 40% reduction in the autopsy rate [14] and other studies in the literature [15][16][17].…”
Section: Discussion and Literature Reviewmentioning
confidence: 63%
“…In their study M. O'Rahelly et al observed a 40% reduction in the autopsy rate [14] and other studies in the literature [15][16][17].…”
Section: Discussion and Literature Reviewmentioning
confidence: 63%
“…Про частоту проведення автопсій у померлих новонароджених не повідомлялося. Було лише зазначено, що частота автопсій у загальній групі пацієнтів відділень інтенсивної терапії протягом періоду спостереження становила 25 %, ця частота знизилась на 40 % з 2000-2002 років частково через небажання сімей давати згоду, частково через небажання медичного персоналу обговорювати перспективу розтину з родинами [19].…”
Section: результати та обговоренняunclassified